Leader Influences On Training Effectiveness Of Construction Professionals: The Case Of Nigeria - N., Onukwube Henry (Penerbit Universiti Sains Malaysia, 2012)
The purpose of this study is to examine how the relationship between leaders and employees under them (leader–member exchange, LMX) impact training transfer, training maintenance and training generalisation of employees that has been trained on various continuous professional development programmes. Using a survey research, 160 construction professionals that have attended continuous professional development (CPD) programmes of their respective professional bodies were asked to respond to the structured questionnaires. Direct supervisors of sampled respondents were also interviewed to corroborate the responses of their followers. The data generated were subjected to both inferential and descriptive statistics. The findings in this study indicates that LMX, training motivation and outcome expectancy are positively related to training effectiveness. The practical contributions of this study are twofold: The first has to do with leadership. The professional who has a good relationship with his or supervisor stands a much better chance of benefitting from the training. Secondly, leaders can directly influence their employees' training motivation and this has a positive impact on how they transfer new skills, maintain them over time and how they use them in other domains of their jobs.